2004
DOI: 10.1186/bcr880
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of interval cancers and implications for disclosure of audit

Abstract: Twenty-five years after its first description the p53 protein has been shown to play a key role in both cancer and ageing. The p53 protein is activated by many different stress pathways, including oncogene action and DNA damage. The elucidation of the p53 response, which is aberrant in most cancers (including breast, lung, stomach and colorectal cancer), has provided many new targets for drug development and p53 gene therapy is now approved in China. In tumours where p53 is mutant small molecules may be able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among the articles included, no study was identified that completed a radiological review for the purposes of open disclosure. A conference abstract prepared by Turnbull and Bagnall [17] conducted a reclassification of 470 interval cancer cases (1989 -2002) within the South Derby Screening Programme, to address guidelines for disclosure of audit for interval breast cancers. Their findings showed a reduced number of interval cancers classified as 'suspicious features / false negative' compared to an older classification system that had been previously applied [17].…”
Section: Open Disclosure and Interval Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the articles included, no study was identified that completed a radiological review for the purposes of open disclosure. A conference abstract prepared by Turnbull and Bagnall [17] conducted a reclassification of 470 interval cancer cases (1989 -2002) within the South Derby Screening Programme, to address guidelines for disclosure of audit for interval breast cancers. Their findings showed a reduced number of interval cancers classified as 'suspicious features / false negative' compared to an older classification system that had been previously applied [17].…”
Section: Open Disclosure and Interval Cancersmentioning
confidence: 99%
“…A conference abstract prepared by Turnbull and Bagnall [17] conducted a reclassification of 470 interval cancer cases (1989 -2002) within the South Derby Screening Programme, to address guidelines for disclosure of audit for interval breast cancers. Their findings showed a reduced number of interval cancers classified as 'suspicious features / false negative' compared to an older classification system that had been previously applied [17]. Further, findings by Jenkins and colleagues [18] conducted within the East Midlands breast screening programme completed a "retrospective, observational audit to assess outcomes from the screening programme in the East Midlands in terms of screen-detected and interval cancers with previous film-reading history".…”
Section: Open Disclosure and Interval Cancersmentioning
confidence: 99%